Improved charge extraction through interface engineering for 10.12% efficiency and stable CsPbBr3 perovskite solar cells. Issue 40 (6th October 2020) - Zhu, Jingwei; Tang, Mixue; He, Benlin; Zhang, Wenyu; Li, Xueke; Gong, Zekun; Chen, Haiyan; Duan, Yanyan; Tang, Qunwei
Abstract : By improving the charge extraction and reducing charge recombination as well as energy loss, interface engineering helps the CsPbBr3 PSC to achieve the best PCE as high as 10.12% and excellent long-term stability. Abstract : The favorable contact and matching energy level at the electrode/perovskite interface as well as the high-quality perovskite film are prerequisites for high photovoltaic performance perovskite solar cells (PSCs). Herein, an innovative interface engineering strategy has been proposed to modify TiO2 as well as the perovskite film simultaneously by introducing ammonium chloride (AC), which not only improves the contact and energy level matching at the TiO2 /perovskite interface but also provides a high-quality perovskite film with larger grain size by regulating the crystallization kinetics of CsPbBr3 . Furthermore, chlorine anions in AC tend to combine with TiO2 to passivate its surface defects; the ammonium cation can bond with the uncoordinated ionic defects of perovskite. As a result, a remarkably enhanced charge extraction and retarded charge recombination within inorganic CsPbBr3 PSCs is acquired through the interface engineering of AC, and the power conversion efficiency of the modified device is increased from the original 6.59% to 9.60%. By compensating the energy level at the perovskite/carbon interface by setting an efficient hole-transporting layer of zinc phthalocyanine (ZnPc), the best efficiency up to 10.12% was achieved for the device with AC and ZnPc interface modification, which is much higher than 7.87% efficiency for the ZnPc-only PSCs, further demonstrating the important positive effects of AC modification on device performance. Moreover, the optimized device without any encapsulation presents an exceptional long-term stability under persistent attack by 80% RH air atmosphere at 25 °C for 720 h.